2019
DOI: 10.29278/azd.555195
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of controlled atmosphere storage and postharvest ozone treatment on storage life and quality of pomegranate

Abstract: *This study is a part of first author master's thesis. The study was presented as an oral presentation in the 11 th International Frutic Symposium (Optimizing Water Use in the Supply Chain of Fresh Produce and printed as a summary).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
2
2
0
1
Order By: Relevance
“…On the other hand, increased gas permeability of leaves with higher doses, as mentioned in the weight loss section, can be reason of higher respiration rates. In the present study, the suppressing effect of 0.5 ppm ozone on respiration rate is accordance with the findings of previous researchers who reported that ozone treatments decreased respiration rates by delaying metabolic activity and senescence processes in different horticultural crops during storage (Zhang et al, 2005;Bolel et al, 2019a;2019b). The positive effect of ozone on respiration rate can also be attributed to its ability to increase systemic resistance in crops by increasing antioxidant capacity, which may suppress respiration processes in cell (Artes-Hernandez et al, 2007).…”
Section: Respiration Ratesupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, increased gas permeability of leaves with higher doses, as mentioned in the weight loss section, can be reason of higher respiration rates. In the present study, the suppressing effect of 0.5 ppm ozone on respiration rate is accordance with the findings of previous researchers who reported that ozone treatments decreased respiration rates by delaying metabolic activity and senescence processes in different horticultural crops during storage (Zhang et al, 2005;Bolel et al, 2019a;2019b). The positive effect of ozone on respiration rate can also be attributed to its ability to increase systemic resistance in crops by increasing antioxidant capacity, which may suppress respiration processes in cell (Artes-Hernandez et al, 2007).…”
Section: Respiration Ratesupporting
confidence: 93%
“…In agreement with our findings, ozone treatment delayed sensory quality losses in different fruit and vegetables compared to control samples during storage (Beltran et al, 2005;Çakir et. al., 2014;Uner et al, 2018;Bolel et al, 2019b). In the present study, shelf life studies in ambient condition showed a decrease in external appearance scores compared to cold storage, and the decrease was more evident after 15+1 days.…”
Section: Sensory Analysissupporting
confidence: 58%
“…Various combinations of CA storage were effective for controlling CI in pomegranates. The most successful combination was 5% CO 2 + 3% O 2 and 15% CO 2 + 5% O 2 [ 129 , 130 ].…”
Section: Factors Affecting Chilling Injury Incidencementioning
confidence: 99%
“…Depolama başlangıcında ve her analiz döneminde (tekerrürde 12 adet) 6 panelist tarafından depodan çıkartılan narlarda kabuk yüzeyindeki buruşma, kırışma ve köşeleme gibi bozukluklar dikkate alınarak dış görünüşleri 1-9 skalasına (1-3: pazarlanamaz, 5:pazarlanabilir, 7: iyi, 9: çok iyi) göre değerlendirmiştir. Narların tat değerleri ise 1 -5 skalasına (1: çok kötü, 2: kötü, 3: orta, 4: iyi, 5: çok iyi) göre puanlandırılmıştır (Bolel, 2019b).…”
Section: Dış Görünüş Ve Tatunclassified